Carbon brainprint – An estimate of the intellectual contribution of research institutions to reducing greenhouse gas emissions - Chatteron, Julia C.; Parsons, David J.; Nicholls, John R.; Longhurst, Philip J.; Bernon, Mike; Palmer, Andrew; Brennan, Feargal P.; Kolios, Athanasios; Wilson, Ian; Ishiyama, Edward; Clements-Croome, Derek; Elmualim, Abbas; et al. (Elsevier, 2015)
Research and innovation have considerable, currently unquantified potential to reduce greenhouse gas emissions by, for example, increasing energy efficiency. Furthermore, the process of knowledge transfer in itself can have a significant impact on reducing emissions, by promoting awareness and behavioural change. The concept of the ‘carbon brainprint’ was proposed to convey the intellectual contribution of higher education institutions to the reduction of greenhouse gas emissions by other parties through research and teaching/training activities. This paper describes an investigation of the feasibility of quantifying the carbon brainprint, through six case studies. The potential brainprint of higher education institutes is shown to be significant: up to 500 kt CO2e/year for one project. The most difficult aspect is attributing the brainprint among multiple participants in joint projects.
Keywords: Carbon brainprint; Carbon footprint; Universities; Research; Higher education; Greenhouse gas